A Singal Case Studyon Coccygodynia - Parmar, Dr. Damini; Shah, Dr. Harshit; Padadharia, Dr.Dhruval; Kanani, Dr. Dipa; Panchal, Dr. Sonal (Asian Journal of Pharmaceutical Research and Development, 2024)
Pain in the coccyx region is known as coccydynia or coccygodynia. Coccygeal pain has been documented since the 16th century, according to Simpson, coccygeal pain has been recognised for hundreds of years, treating it can be challenging and occasionally contentious due to the complex nature of coccygeal pain. Its genesis is influenced by numerous physiological and psychological factors. With or without conservative treatment, most occurrences of coccydynia recover within weeks to months, but in a small number of people, the pain can last a long time and be incapacitating. Female gender and obesity have been linked to an increased chance of acquiring the condition. The anatomy, physiology, diagnosis and therapy of coccydynia are briefly discussed in this Study. For individuals with intractable coccyx discomfort, a multidisciplinary strategy including physical therapy, ergonomic modifications, drugs, injections, and potentially psychotherapy has the best chance of recovery. A 26 years old Female patient came in OPD with Symptoms of Pain and tenderness in coccyx region, aggravated with sitting position. In past history a patient is fall down from vehicle in direct vertical position, at this incidous mild discomfort in lower back region, after that gradually increase pain in coccyx region within two days. Patient could not able to seat proper and pain remain constant. So, she came to Govt. Akhandanand Hospital for ayurvedic treatment.The patient was treated with ayurvedic medicines Yogaraj Guggulu, Dashmoolkwath, Tab.bocomo and advise to take sitz bath with luke warm water and use wedge shape cushion on sitting position. The patient was advised to follow up initially after 7 days and later after every 15thdays. After 7 days there were mild pain and no tenderness. After that pain gradually decrease. The pain was completely gone on the third follow up and no any other complaints related to coccydynia.